The Formation and Evolution of Interorganisational Business Networks in Megaprojects: A Case Study of Chinese Skyscrapers - Yujie Lu; Wei Wei; Yongkui Li; Zhilei Wu; Hao Jin (Complexity)
Megaprojects are implemented by different organisations, such as owners, consultants, and contractors. Gradually, these organisations and their connections can form business networks that influence both the market position of individual organisations and project performance. Previous research on large-scale projects mainly focused on static and homogeneous networks that were constructed by one individual project and/or carried out over one-off collaboration. However, this neglected the consideration of project network diversity, as well as repetitive, dynamic, cross-project coopetition relationship (i.e., collaboration and competition) and long-term business networks formed by key actors. Here, we chose Chinese skyscrapers over 300 meters that were built from 1996 to 2015 as typical megaproject cases and analysed the formation and evolution of megaproject business networks from the perspective of interorganisational coopetition. We identified the key actors involved and empirically studied their dynamic network positions over time. The main contributions of this study are threefold. First, we found that past collaboration experience has direct and dynamic impacts on the formation of megaproject business networks. Second, we identified key actors in the interorganisational business network and unveiled their dynamic positions with clear patterns. Third, we highlighted the temporal-spatial effect on the formation and development of business networks, alongside developments in the megaproject market. The findings of this study also provide practical applications for owners to choose collaboration partners and to build high-performance teams and for suppliers to enter and sustain the business in the megaprojects networks.